FAKTOR UTAMA YANG MEMPENGARUHI NASABAH DALAM MENGAMBIL KREDIT DI BANK PERKREDITAN RAKYAT (BPR) KOTA KEDIRI - Edy Djoko Soeprajitno; Wawan Herry Setyawan; Dhiyan Septa Wihara (UNIVERSITAS PGRI MADIUN, 2019)
One of the objectives of credit is to move the wheels of the regional economy. Especially for the small and medium enterprises (SMEs) trade and micro sector, which is now booming because it can improve the household economy. Various financial institutions offer various types of loans with attractive facilities and according to the needs of the target market. Therefore, today's society is demanded to be smart in accessing credit at bank financial institutions. Including the People's Credit Bank (BPR) Kota Kediri which also competes in offering loans that are in accordance with the wishes of the people in the Kediri region and its surroundings. The sample used in this study amounted to 97 customers. This study uses a quantitative approach with factor analysis techniques using principal component analysis (PCA). The result is that there are six groups of factors that influence customers in taking credit with a cumulative diversity value of 59,671. Factor I consists of variations in time period, loan nominal and service has an eigenvalue of 2.935 and total diversity value of 18.343%. Factor II consisted of reasons for interest rates, repayment deductions and requirements having an eigenvalue of 1.590 and a total diversity of 9.936%. Factor III consisted of variations in interest rates and flexible time periods having eigenvalues of 1.552 and total diversity of 9.701%. Factor IV consists of a credit process and the service schedule has an eigenvalue of 1.2282 and a total diversity of 8.014. Factor V consists of loans as needed and flexible guarantees have an eigen value of 1.165 and a total diversity of 7.284. Factor VI is a lack of requirements following with an eigen value of 1.023 and a total diversity of 6.394.Key words : Decision on taking credit, Factor Analysis, BPR in Kediri City